(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the conceptual foundations and evolution of antitrust policy in the context of economic digitalization. It emphasizes the necessity of adapting traditional approaches to the regulation of market power due to the proliferation of digital platforms, which are characterized by strong network effects, access to vast datasets, and algorithmic advantages. Based on a comparative analysis of international practices in the European Union, the United States, China, Japan, India, and Russia, the paper identifies key features of contemporary antitrust regulation. Special attention is given to the institutional strengthening of competition authorities, the development of new indicators of market dominance, and the coordination of cross-border oversight mechanisms. The article concludes by substantiating the role of antitrust policy as a strategic instrument for sustainable and equitable digital development.